Study of Dust Cavity around the White Dwarf WD 0352-049 in Infrared Astronomical Satellite Map - Paudel, M. S.; Bhandari, P.; Bhattarai, S. (Journal of Nepal Physical Society, 2021)
In this work, we have studied the far-infrared images of the dust cavity around the White Dwarf WD 0352-049 available in Infrared Astronomical Satellite Map from Sky View Observatory. The size of the cavity is 24.48 pc × 8.10 pc. We have studied the relative infrared flux density and calculated the dust color temperature and dust mass. The temperature of the whole cavity structure lies between a maximum value 24.09 ± 0.50 K to a minimum 21.87 ± 0.61K with fluctuation of 2.22 K and an average value of 23.09 ± 1.11 K. The small fluctuation of dust color temperature suggests that the dust in cavity structure is evolving independently and less disturbed from background radiation sources. The color map shows the identical distribution of flux at 60 μm and 100 μm and the inverse distribution of dust color temperature and dust mass. There is a Gaussian-like distribution of relative flux density, dust color temperature and dust mass. The Gaussian distribution of temperature suggests that the dusts in cavity are in local thermodynamic equilibrium. The study of relative flux density and dust color temperature along the major and minor axis shows there is a sinusoidal fluctuation of flux and temperature, which might be due to the wind generated by White Dwarf located nearby the center of the cavity structure. The total dust mass of the dust is found to be 0.07 Mʘ and that of gas is 13.66 Mʘ. The Jeans mass of the structure is less than the total mass of gas in the structure, suggesting the possibility of star formation activity by gravitational collapse in the future. Also, the study of inclination angle suggests that the three-dimensional shape of the structure is uniform and regularly shaped.